A prototype telerobotic platform for live transmission line maintenance: Review of design and development. (July 2018) - Banthia, Vikram; Maddahi, Yaser; Zareinia, Kourosh; Liao, Stephen; Olson, Tim; Fung, Wai-Keung; Balakrishnan, Subramaniam; Sepehri, Nariman
This paper reports technical design of a novel experimental test facility, using haptic-enabled teleoperation of robotic manipulators, for live transmission line maintenance. The goal is to study and develop appropriate techniques in repair overhead power transmission lines by allowing linemen to wirelessly guide a remote manipulator, installed on a crane bucket, to execute dexterous maintenance tasks, such as twisting a tie wire around a cable. Challenges and solutions for developing such a system are outlined. The test facility consists of a PHANToM Desktop haptic device (master site), an industrial hydraulic manipulator (slave site) mounted atop a Stewart platform, and a wireless communication channel connecting the master and slave sites. The teleoperated system is tested under different force feedback schemes, while the base is excited and the communication channel is delayed and/or lossy to emulate realistic network behaviors. The force feedback schemes are: virtual fixture, augmentation force and augmented virtual fixture. Performance of each scheme is evaluated under three measures: task completion time, number of failed trials and displacement of the slave manipulator end-effector. The developed test rig has been shown to be successful in performing haptic-enabled teleoperation for live-line maintenance in a laboratory setting. The authors aim at establishing a benchmark test facility for objective evaluation of ideas and concepts in the teleoperation of live-line maintenance tasks.